Analisa Potensi Tempat Ibadah Untuk Pemberdayaan Ekonomi Masyarakat - Luluk Latifah; Iskandar Ritonga; Lutfi Agus Salim; Fatkur Huda (LPPM Sekolah Tinggi Ilmu Ekonomi Al-Washliyah Sibolga, 2023)
One of the big problems facing the Indonesian nation at this time is the problem of poverty and poverty. One of the solutions to prevent and at the same time overcome poverty is the development of a people's economy that is fair and equitable based on prosperity, which is far from capitalism and socialism but respects ownership of individual rights and at the same time maintains shared ownership. The purpose of this research is to find answers about the potential for the existence of places of worship in empowering the community's economy. The method used in this study is a descriptive qualitative method with a content analysis approach and library research to find out the conclusions from a text, journal or literature and research results or data sources that have been collected. The results obtained are that places of worship consisting of mosques, churches, monasteries, temples and temples have great potential in empowering the economy of their people. The economic empowerment of the people from each place of worship will have implications for the economic empowerment of the community around the place of worship as well so that by moving the community's economic empowerment, the wheels of the economy will spin more broadly and this moving economy will have a positive influence on the income of the place of worship, especially the community as a whole. general and ultimately the economy as a whole, so that this will prevent poverty.